2016
DOI: 10.1055/s-0035-1551545
|View full text |Cite
|
Sign up to set email alerts
|

Transorbital Orbitocranial Penetrating Injury with an Iron Rod

Abstract: Transorbital orbitocranial penetrating injuries (TOPIs) are relatively rare, can be caused by high-speed projectile foreign bodies to low-energy trauma (which is rarer), and account for 24% of penetrating head injuries in adults and approximately 45% in children. We report an uncommon nonfatal case of TOPI where a 16-year-old male child sustained injury due to accidental penetration of metal bar into the forehead. A bicoronal flap was raised to remove the metal bar. The patient recovered well, had normal visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Eight case reports involving nine patients with steel rod impalement injuries involving the spine were identified in an extensive review of the English literature on PubMed (Table 1). We concluded that steel rod impalement injuries sparing the spine are not extremely rare, with different entrance sites, such as the oral cavity, [2] orbita, [3] nose, [4] cranium, [5] neck, [6] thorax, [7] abdomen, [8] hand, [9] rectum, [10] buttock, [11] and groin. [12] Most victims of steel rod impalement injuries are construction workers, and we believe that occupational safety specialists have to focus on this type of injury to decrease the incidence of this mostly preventable condition.…”
Section: Discussionmentioning
confidence: 92%
“…Eight case reports involving nine patients with steel rod impalement injuries involving the spine were identified in an extensive review of the English literature on PubMed (Table 1). We concluded that steel rod impalement injuries sparing the spine are not extremely rare, with different entrance sites, such as the oral cavity, [2] orbita, [3] nose, [4] cranium, [5] neck, [6] thorax, [7] abdomen, [8] hand, [9] rectum, [10] buttock, [11] and groin. [12] Most victims of steel rod impalement injuries are construction workers, and we believe that occupational safety specialists have to focus on this type of injury to decrease the incidence of this mostly preventable condition.…”
Section: Discussionmentioning
confidence: 92%
“…[10][11][12][13][14] Apart from the injuries to facial skeleton, penetrating craniofacial injuries can lead to damage to orbit and its contents, cerebrospinal fluid (CSF) leak and its sequel (risk of meningitis or abscess), intracranial hematomas, injury to neurovascular structures, and retained foreign bodies. 11,12,[15][16][17][18][19][20][21][22] Indian J Neurotrauma:2020;17:143-145…”
Section: Discussionmentioning
confidence: 99%
“…10,21,[25][26][27][28] The outcome of craniofacial penetrating injuries depends on the mechanism of injury and the underlying damage to neurovascular structures. 10,17,22,24 If there is no major damage to these structures, the patients with penetrating craniofacial trauma have favorable outcome. 10,17,22…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These injuries can lead to minor penetrating entry wounds to massive external wounds associated with extensive tissue damage. [1][2][3][4][5][6][7][8][9][10][11][12] The extent of injuries depends on the size, shape, velocity (low vs. high) of penetrating object, site, and area of contact at the time of impact. 19,20 As we observed in the presented case, if a person is involved in motor vehicle accident, the associated fall can add to the extent and severity of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition to massive injury to the facial tissue and craniofacial skeleton, there may be retained foreign-body fragments that will add to the difficulty in the management of these patients. [1][2][3][4][5][6][7][8][9][10][11][12] We present a case of man who sustained massive penetrating craniofacial injuries due to polyvinyl chloride (PCV) pipe and discuss the management.…”
Section: Introductionmentioning
confidence: 99%